Mathematics Learning as a Means of Internalizing Aqidah: A Critical Analysis of Islamic Education Literature - Aisyah, Aisyah; Bianqi, Zabrina; Kusno, Kusno (Yayasan Rahmat Islamiyah, 2026)
This study aims to critically examine the relationship between mathematics and tawhid (Islamic monotheism) and to explore how fundamental mathematical concepts can serve as a means of internalizing aqidah within the framework of Islamic education. This research employs a qualitative descriptive approach through a systematic literature review. Data sources consist of relevant journal articles, academic books, and conference proceedings published within the last ten years that discuss the integration of mathematics, Islamic values, and tawhid. The collected literature was analyzed thematically to identify patterns, concepts, and theoretical perspectives regarding the relationship between mathematical structures and monotheistic principles. The findings indicate that mathematical concepts such as numbers, patterns, logical consistency, order, and symmetry reflect the principles of divine unity, harmony, and precision inherent in tawhid. These concepts can be interpreted as manifestations of Allah’s order (sunnatullah), thereby positioning mathematics as not merely a computational tool but also a medium for strengthening students’ spiritual awareness and religious character, including honesty, discipline, and accuracy.